PENGARUH HEDONIC SHOPPING MOTIVATION, STORE ATMOSPHERE DAN SALES PROMOTION TERHADAP IMPULSE BUYING (SURVEY: PADA KONSUMEN KOSMETIK TRANSMART KOTA PADANG) - Hanifah Syafri; Eri Besra (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This research was conducted to understand the influence of hedonic shopping motivation, store atmosphere and sales promotion on the impulse buying survey of cosmetics consumers at Transmart in Padang. To determine the sample in this study using simple random sampling with criteria, (a) Women who shop cosmetics at Transmart Padang, (b) Consumers of women who have jobs, so they already have income, (c) Aged 17 years and above and are considered able to provide information correctly and accurately. This study uses a sample size of 120 respondents obtained from the Hair method. This study uses quantitative methods and survey methods in collecting data about attitudes, feelings, past behavioral beliefs and planned behavior that are assisted by SPSS 16.0. The results of this study reveal that hedonic shopping motivation has a significant effect on impulse buying in cosmetic consumers Transmart Padang, store atmosphere has a significant effect on impulse buying in Transmart Padang cosmetics consumers, sales promotion has a significant effect on impulse buying in cosmetics consumers Transmart Padang.